Strategy for the development of tourism as a tool for planning at a local level: The example of Karlino commune (West Pomeranian Voivodeship) - Szostak, Daniel; Głąbiński, Zbigniew; Duda, Tomasz (Turyzm/Tourism, 2020)
The study aims to analyse the correlation between planning tourism development at the local level and the development of the space that is being planned. Another goal is to determine the role of the local authorities (of the Karlino commune – gmina) in the implementation of strategic activities and the integration of various local beneficiaries around such activities. Further it will analyse how elaborating and implementing tourism development strategies may contribute to the local tourism economy and indicates the role and place of strategic planning in the process of creating and developing the tourist potential of a commune with particular emphasis on Karlino. The paper also discusses the tourism policy of Karlino’s local government as well as the strategic goals to be implemented and indicates its tourism development directions. The following research methods have been applied: expert method, observation method (using the inventory technique, physical inventory of the elements of the analysed space and actions taken), monographic method, document research, diagnostic survey analysis (using the survey technique of institutions from the examined area: Karlino commune, the communes of the Białogard powiat, the municipalities of the Association of Towns and Communes in the Parsęta Valley), and a critical literature review. The case of Karlino commune and its strategic activities in the field of tourism indicates that planning constitutes one of the most effective tools for local development. Such activity particularly shows that the commune can and wants to direct its socio-economic development based on optional (rather than obligatory) activities focused around the strategic use of endogenous resources. The paper indicates strategic action directions based on an inventory of such available endogenous resources. It shows how the local tourism economy may benefit from a tourism development strategy.